An optimized transfer learning approach integrating deep convolutional feature extractors for malaria parasite classification in erythrocyte microscopy - Reddy, C. Kishor Kumar; Anisha, P. R.; Almushharaf, Ahlam; Talla, Radhika; Baili, Jamel; Cho, Yongwon; Nam, Yunyoung (Frontiers in Medicine, 2025)
BackgroundMalaria, caused by Plasmodium parasites transmitted through bites from infected female Anopheles mosquitoes, results in severe symptoms such as anemia and potential organ failure. The high prevalence of malaria necessitates reliable diagnostic methods to reduce the workload of microscopists, particularly in resource-limited settings.MethodsThis paper evaluates the efficacy of an ensemble learning approach for automated malaria diagnosis. The proposed model integrates convolutional ensemble methods, combining outputs from transfer learning architectures such as VGG16, ResNet50V2, DenseNet201, and VGG19. Data augmentation and pre-processing techniques were applied to enhance robustness, and the ensemble approach was fine-tuned for optimal hyperparameters.ResultsThe ensemble achieves a test accuracy of 97.93% by combining a evidence of CNN with multiple transfer learning models (VGG16, ResNet50V2, DenseNet201, and VGG19), with an F1-score and precision of 0.9793 each, outperforming standalone models like Custom CNN (accuracy: 97.20%, F1-score: 0.9720), VGG16 (accuracy: 97.65%, F1-score: 0.9765), and CNN-SVM (accuracy: 82.47%, F1-score: 0.8266). The method demonstrated effectiveness in classifying parasitized and uninfected blood smears with high reliability, addressing the limitations of manual microscopy and standalone models.ConclusionThe proposed ensemble learning approach highlights the potential of integrating transfer learning models to improve diagnostic accuracy for malaria detection. This scalable, automated solution reduces reliance on manual microscopy, making it highly applicable in resource-constrained settings and offering a significant advancement in malaria diagnostics.